Deduced primary structure of the alpha subunit of the GTP-binding stimulatory protein of adenylate cyclase. - Robishaw, J D (1986)
A bovine adrenal cDNA clone encoding the entire alpha subunit of the GTP-binding regulatory protein that stimulates adenylate cyclase (Gs) was isolated and sequenced. This cDNA directed the synthesis of the larger, 52-kDa form of the polypeptide in COS cells, even though the clone appeared to encode a 46-kDa protein. Comparison of the deduced amino acid sequence of Gs alpha with the alpha subunit of another G protein, transducin, revealed striking homologies.